Synthesis And Characterization Of Lithium-Modified Mesoporous Catalyst For Solvent-Free Selective Oligomerization Of Glycerol To Diglycerol - Ayoub, Muhammad (2013)
Biodiesel industry leads to the generation of about 10% glycerol as a co-product, which affects the overall biodiesel economy. This study examines a process for converting glycerol to a higher value product i.e. diglycerol via a solvent free base-catalyzed oligomerization process. The catalytic activity of different homogeneous alkali catalysts (LiOH, NaOH, KOH and Na2CO3) and heterogeneous catalysts (with different supports i.e. USY, SBA-15 and montmorillonite K-10 clay) was investigated and with the aim of improving the yield and selectivity to the desired product. The prepared solid catalysts were characterized to study their textural properties and their surface morphology using BET, SEM, EDX, TEM, FTIR, TGA, XRD, SAXS, and ICP-AES while Hammet indicator was used for characterizing their basic strength. LiOH exhibited high catalytic activity as indicated by almost complete glycerol conversion (99 %) but with poor selectivity (18%) towards diglycerol. Clay Li/USY was found to be active for glycerol conversion (98 %) with good polyglycerol yield (72 %) but the diglycerol selectivity was still rather low (29 %) under the same reaction conditions. SBA-15 experienced severe structural collapse after the alkali loading but the stability was improved with suitable amount of magnesium coating prior to lithium loading. 90 % glycerol conversion and 59 % polyglycerol yield were observed but the selectivity to diglycerol was observed at only 14 % for the Li10-Mg30/SBA-15 catalyst. Lithium modified montmorillonite K-10 (Clay Li/MK-10) was then prepared and its activity was investigated.High conversion of glycerol (86 %) and high selectivity to diglycerol (68 %) were observed under the same reaction conditions. The reaction behaviors for all prepared catalysts were also investigated based on the formation of diglycerol isomers (αα’, ββ’ and αβ isomers) in the final product mixture. Among the catalysts prepared, Clay Li/MK-10 was the most active one. Effect of various process conditions including the catalyst loading, reaction time and temperature were investigated using response surface methodology (RSM). The optimum conditions were found to give 61 % of diglycerol yield at 240 oC of reaction temperature with 3.35 wt % of catalyst and about 7 h of reaction time. Clay Li/MK-10 could also be reused but it experienced an activity drop of about 30.6 % after the first run. A mathematical model was successfully developed for most active catalyst Clay Li/MK-10. Low activation energy of 1.550 kJ/ mol was observed over this catalyst for the glycerol oligomerization reaction. In short, the Clay Li/MK-10 was an effective catalyst for the glycerol oligomerization process to diglycerol production. Industrially, the findings attained in this study might contribute towards promoting the biodiesel industry through utilization of its glycerol by-product in the form of highly valuable diglycerol.